Controle postural como um sistema complexo : análise de distribuição das velocidades do centro-de-pressão - Santos, Edenize Sodré dos (2015)
In the present study, we investigated patterns in the postural sway that characterize the static balance in human beings through distribution of center-of-pressure (COP) velocities. To measure the postural sway, sixteen healthy young subjects performed tasks stance upright under force platform in three conditions of open eyes: bipedal, right unipedal and left unipedal stances. We collected the COP trajectory for each trial. From these trajectories, we obtained the COP velocities. Firstly, we verified that the velocity distributions exhibit non-Gaussian behavior and can be approximated by generalized Gaussians with fat tails. We also discussed possible implications of modeling COP velocity by using generalized Fokker-Planck equations related to Tsallis statistics and Richardson anomalous diffusion. The models of generalized Gaussian distributions were, in general, sensitive to detect differences between bipedal and unipedal stances. By using another database (available to the public), we repeated the analysis to investigate the distribution of COP velocities in a group of young in comparison with elderly in the bipedal position and closed eyes. All the results pointed to the existence of a universal behavior for the distribution of velocities.